Governing Digital Markets: Institutional Architecture and Structural Power - Lina Marlina (UDEX Institute, 2025)
Digital markets are increasingly structured by institutional architecture and structural power rather than technological novelty alone. Governance devices—regulatory consolidation, data localization, interoperability standards, and compliance infrastructures—reshape ecosystem configuration, dependence relations, and surplus allocation. By integrating institutional theory, ecosystem strategy, and resource dependence logic, this collection advances a governance-centered perspective on digital competition in emerging economies.